Awakening the management of coworking spaces - Bouncken, Ricarda B., 1969- (Emerald Publishing Limited, 2023)
In Awakening the Management of Coworking Spaces, the chapter authors combine a scientific approach with managing implications, developing theoretic constructs, reporting qualitative and quantitative findings about challenges, potentials, effects, managerial solutions, and success stories.